2016
DOI: 10.3945/ajcn.115.124586
|View full text |Cite
|
Sign up to set email alerts
|

Association of body mass index and survival in pediatric leukemia: a meta-analysis

Abstract: Background: Obesity is a worldwide epidemic in children and adolescents. Adult cohort studies have reported an association between higher body mass index (BMI) and increased leukemiarelated mortality; whether a similar effect exists in childhood leukemia remains controversial. Objective: We conducted a meta-analysis to determine whether a higher BMI at diagnosis of pediatric acute lymphoblastic leukemia (ALL) or acute myeloid leukemia (AML) is associated with worse event-free survival (EFS), overall survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 47 publications
5
111
1
4
Order By: Relevance
“…The disease process might plausibly contribute to the classification of a smaller proportion as overweight, or the geographic and ethnic distribution of our cohort may be responsible. These findings are intriguing and are the focus of ongoing analysis, particularly in the light of recent data correlating BMI percentile with mortality in children with ALL [8,10]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease process might plausibly contribute to the classification of a smaller proportion as overweight, or the geographic and ethnic distribution of our cohort may be responsible. These findings are intriguing and are the focus of ongoing analysis, particularly in the light of recent data correlating BMI percentile with mortality in children with ALL [8,10]. …”
Section: Discussionmentioning
confidence: 99%
“…The impact of obesity is not trivial. Recent meta-analyses found that the presence of obesity at diagnosis is a poor prognostic indicator in children and adults with leukemia [810]. In children with leukemia, those classified as obese at diagnosis have a 35% increased risk of mortality compared with those who are not obese [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of overweight might be underestimated because having a higher BMI at diagnosis is associated with poorer survival. This could have resulted in excluding more overweight CCSs due to our exclusion criteria of ≥5 y of survival after initial diagnosis of cancer (39). Furthermore, our results could have been biased by reverse causation (e.g., a lack of sports participation could have been due to overweight).…”
Section: Strengths and Limitationsmentioning
confidence: 91%
“…Maintenance of osteoblast numbers during leukemia by pharmacological inhibition of the synthesis of duodenal serotonin through treatment with a tryptophan hydroxylase inhibitor stimulates normal hematopoiesis, delays disease engraftment, reduces tumor burden, and prolongs survival (Krevvata et al, 2014). Castillo et al, 2016;Castillo et al, 2012;Orgel et al, 2016;Orgel et al, 2014 Sequester and metabolize commonly used chemotherapeutic drugs Behan et al, 2009;Pramanik et al, 2013;Sheng et al, 2017Sheng et al, 2017 Secrete glutamine: inhibits the activity of L-asparaginase, a common treatment for ALL Ehsanipour et al, 2013 Fuel AML blasts survival by production of free fatty acids Shafat et al, 2017;Ye et al, 2016;Li et al, 2018Shafat et al, 2017 Lepr + Esm1 + perivascular cells…”
Section: Osteolineage Cellsmentioning
confidence: 99%